The Impact of Positive and Negative Income Changes on the Height and Weight of Young Children - Thomas Buser; Hessel Oosterbeek; Erik J. S. Plug; Juan Ponce; José Rosero (Institute for the Study of Labor (IZA), 2014)
We estimate the impact of changes in unearned income on the height and weight of young children in a developing country. As source of variation we use changes in the eligibility criteria for receipt of an unconditional cash transfer in Ecuador. Two years after families lost the transfer, which they had received for seven years, their young children weigh less, and are shorter and more likely to be stunted than young children in families that kept the cash transfer. We find no effect on young children's height and weight two years after gaining the cash transfer. Information on household expenditures suggests that a reduction of food expenditures by households that lost the transfer is the main mechanism behind this finding.
Keywords: I14; H51; C31; 330; cash transfers; health outcomes; developing country; poverty reduction